Active Sliding Mode Control Antisynchronization of Chaotic Systems with Uncertainties and External Disturbances - Wafaa Jawaada; M. S. M. Noorani; M. Mossa Al-sawalha (Journal of Applied Mathematics)
The antisynchronization behavior of chaotic systems with parametric uncertainties and external disturbances is explored by using robust active sliding mode control method. The sufficient conditions for achieving robust antisynchronization of two identical chaotic systems with different initial conditions and two different chaotic systems with terms of uncertainties and external disturbances are derived based on the Lyapunov stability theory. Analysis and numerical simulations are shown for validation purposes.